2022
DOI: 10.3390/geosciences12030116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of InfraRed Thermography Supported by UAV and Field Surveys for Rock Mass Characterization in Complex Settings

Abstract: The InfraRed Thermography (IRT) technique is gaining increasing popularity in the geosciences. Although several studies on the use of this technique for rock mass characterization were reported in the literature, its applicability is challenging in complex environments, characterized by poor accessibility, lithological heterogeneity, karst features and disturbances, such as vegetation and human activities. This paper reports the results of specific tests carried out to explore the application of IRT methods, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The authors also mention about the constraints of the IRT method. Application of IRT for rock mass characterization in complex environments is discussed in [86], In this paper, the challenges expected, limitations and advantages of using IRT in a complex environment is discussed in detail.…”
Section: Traunstein Irt Results From Mt Traunstein Corresponds Tomentioning
confidence: 99%
“…The authors also mention about the constraints of the IRT method. Application of IRT for rock mass characterization in complex environments is discussed in [86], In this paper, the challenges expected, limitations and advantages of using IRT in a complex environment is discussed in detail.…”
Section: Traunstein Irt Results From Mt Traunstein Corresponds Tomentioning
confidence: 99%
“…If compared to heat-source detection, TIR images of natural landscapes display weaker contrast driven by different factors: temperature inhomogeneity, surface roughness, physical-chemical composition influencing the optical properties. Indeed, the TIR image contrasts are totally different from those observed in the VIS/NIR [16][17][18][19][20]. Finally, the penetration of TIR radiation through fog and rain is typically better than that of VIS/NIR light [9], although certainly not comparable to that of radars [21].…”
Section: Introductionmentioning
confidence: 92%
“…It is generally believed that thermal infrared imaging can only identify direct sources of heat, such as living beings or engines in operation, or, to enter the domain of geological risk monitoring, volcanic eruptions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] or geothermal heat sources [29]. In the specific case of landslide monitoring, infrared thermography has been used to characterize either the different types of terrains within a landslide area [13,15] or the thermal and mechanical properties of rocky walls [8,17,30], as we also do here.…”
Section: Physical Modelmentioning
confidence: 99%
“…It is shown that by combining different kinds of technologies, IRT could be used to further monitor rock cliffs and assess rock properties remotely. Other studies adopting both IRT and a UAV provided successful cases for aspects such as erosion monitoring of a river embankment [29], detecting weathering and degradation of tuff cliffs [30], and qualitative rock mass evaluation [31]. However, data collection in these studies was conducted separately by UAV and ground-based IRT, which did not fully utilize the potential of combining a UAV and IRT.…”
Section: Recent Studies On Natural Terrain Survey Using Irtmentioning
confidence: 99%